Modelling surface roughness of enzyme layer of amperometric biosensors - Ivanauskas, Feliksas; Baronas, Romas; Kulys, Juozas; Sapagovas, Mifodijus (Lietuvos matematikos rinkinys, 2003)
A mathematical model of amperometric biosensors is presented. The model is based on the diffusion equations containing a non-linear term related to the Michaelis-Menten kinetics of the enzyme reaction. The model takes into concideration surface roughness of the enzyme layer. Using digital simulation, the influence of the geometry of the roughness on the biosensor response was investigated. The digital simulation was carried out using the finite difference technique.